Pancreatic safety of sodium‐glucose cotransporter 2 inhibitors in patients with type 2 diabetes mellitus: A systematic review and meta‐analysis. Issue 2 (4th February 2020) - Tang, Huilin; Yang, Keming; Li, Xin; Song, Yiqing; Han, Jiali
Abstract: Purpose: This study aimed to systematically evaluate the association between sodium‐glucose cotransporter 2 (SGLT2) inhibitors and pancreatic safety in patients with type 2 diabetes mellitus (T2DM). Methods: Electronic databases were searched before September 2019 to include randomized controlled trials (RCTs) of SGLT2 inhibitors that reported any event on pancreatitis or pancreatic cancer among patients with T2DM. Peto odds ratio (OR) with 95% confidence interval (CI) was used to pool the data. The GRADE framework was introduced to assess the quality of evidence. Results: Of the 35 trials involving 44 912 patients with T2DM included, 41 events of acute pancreatitis (19 trials; 32 932 patients), 72 events of overall pancreatitis (including acute pancreatitis, chronic pancreatitis, or nonspecific pancreatitis; 26 trials; 36 688 patients), and 40 events of pancreatic cancer (18 trials; 27 806 patients) were reported during a median follow‐up of 52 weeks. SGLT2 inhibitors were not associated with an increased risk of acute pancreatitis compared to controls (placebo or other active drugs; Peto OR, 1.13; 95% CI, 0.60‐2.13; moderate quality evidence). A similar result was found for risk of overall pancreatitis (Peto OR, 1.08; 95% CI, 0.67‐1.75; moderate quality evidence) and pancreatic cancer (Peto OR, 1.34; 95% CI, 0.71‐2.54; very low‐quality evidence). Conclusions: Moderate quality evidence from RCTs shows no significantly increased risk of acute pancreatitis associated with SGLT2 inhibitors, while there is very low‐quality evidence suggesting no significant association between SGLT2 inhibitors and pancreatic cancer among patients with T2DM.